Stem-cells: prospects for treating dementia. - Ekonomou A; Cedar SH; Ballard CG; Minger SL (British Journal of Neuroscience Nursing, 2008)
Stem cells have the capacity to generate multiple types of differentiated cells (multipotency) and undergo cell divisions in which at least one of the daughter cells maintains stem cell potentialIn the healthy adult brain, endogenous neural stem cells replace neurons in the hippocampus and olfactory bulbAdult neural stem cells can be isolated in the hippocampus and cultured ex vivo for extended periods with potential to differentiate them into neurons, astrocytes or oligodendrocytesIt is hypothesized that mental deterioration in Alzheimer's disease could be slowed and possibly reversed if neurons lost in the progression of the disease could be replaced using stem-cell therapyThe opportunity to enhance endogenous adult neural stem cells' proliferation, migration and differentiation into neurons will have great therapeutic potential for neurodegenerative diseases such as Alzheimer's disease